Data Analysis and Decision Making: A Case Study of Re-accommodating Passengers for an Airline Company. Issue 1 (May 2016) - Chongwatpol, Jongsawas
This case is designed to illustrate the conceptual foundations of business intelligence; thus, the analysts can develop an understanding on how to utilize the business intelligence framework to make proper decisions in the turbulent and competitive business environment. The case started when Bob, the senior vice president of Thai ABC Airline, had to implement a new method of re-accommodating passengers in the case of canceled/delayed flights. The first incident was reported that the flight from Bangkok, Thailand (BKK) to Hong Kong (HKG) was expected to be delayed and seven passengers would definitely miss the original connecting flight from Hong Kong to Chicago, USA. Unfortunately, the next available flight to Chicago was almost fully booked and could accommodate only two more passengers. Thus, Bob and his team had to decide which two passengers should be on the next available flight and which others would have to stay overnight in Bangkok for the morning flight to Chicago on the next day. The following topics are discussed in or raised by the case: (1) Airline Industry and the incidence of passengers' dissatisfaction because of delayed/canceled flights, (2) Business intelligence concept, (3) Customer acquisition and customer retention, (4) Social media and key influencers, and (5) Decision making based on different airline's strategic direction.